ANALISIS READINESS SDM RSU BALI JIMBARAN DALAM MENGHADAPI ERA DISRUPTION - Ari Darma Putra, I Gede; Sri Subawa, Nyoman (Bali International Scientific Forum, 2021)
The development of the times has changed quite rapidly every day, where technology has changed to become more sophisticated, followed by changes in human behavior, making companies in Indonesia, especially in Bali engaged in services such as RSU Bali Jimbaran, to prepare human resources to face disruption its so fast. RSU Bali Jimbaran is a private public hospital located at Jl. Udayana University Campus Number 52 Jimbaran which always prioritizes service and tries to procure medical devices that have the latest technology and prepares a system to simplify the flow of services. This study used a qualitative approach which used six sources consisting of three staff at the Bali Jimbaran Hospital and three patients who used the services of the Bali Jimbaran Hospital. Where the results of this study lead to positive results which state that the staff of Bali Hospital in Jimbaran is ready to face the era of disruption.